2012
DOI: 10.5210/bsi.v21i0.3979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Response Cost and Socially-Assisted Interventions on Hand-Hygiene Behavior of University Students

Abstract: A field study was conducted to examine the effect of interventions to increase hand-hygiene behavior of university students. Student patrons of a university cafeteria were observed during lunch. Across several phases, researchers observed and recorded the number of students (a) entering the restroom to wash hands and (b) using a hand-sanitizer gel. Interventions included an informational poster, hand-sanitizer dispenser, and change agent to increase hand-hygiene behavior. Results showed that the presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Although behavior analysis research offers evidence-based interventions to promote CDC guidelines on reducing disease transmission, an immense opportunity still exists to expand our research contributions. To start, although behavior analysts have researched compliance with basic prevention procedures (e.g., handwashing, cleaning and disinfecting, wearing PPE; Bowman et al, 2019;Casella et al, 2010;Choi et al, 2018;Cruz et al, 2019;Doll et al, 2007;Fournier & Berry, 2012;Geller et al, 1980;Luke & Alavosius, 2011;Martinez-Onstott et al, 2016;Myers et al 2010;Stephens & Ludwig, 2005), limited research exists demonstrating that interventions have achieved sufficient reduction of pathogens (e.g., using objective measures of cleanliness, doffing PPE safely). Thus, behavior analysts can extend their work by using objective measures like pathogen cultures or optic markers and by evaluating the subsequent impact on reported illnesses and attendance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although behavior analysis research offers evidence-based interventions to promote CDC guidelines on reducing disease transmission, an immense opportunity still exists to expand our research contributions. To start, although behavior analysts have researched compliance with basic prevention procedures (e.g., handwashing, cleaning and disinfecting, wearing PPE; Bowman et al, 2019;Casella et al, 2010;Choi et al, 2018;Cruz et al, 2019;Doll et al, 2007;Fournier & Berry, 2012;Geller et al, 1980;Luke & Alavosius, 2011;Martinez-Onstott et al, 2016;Myers et al 2010;Stephens & Ludwig, 2005), limited research exists demonstrating that interventions have achieved sufficient reduction of pathogens (e.g., using objective measures of cleanliness, doffing PPE safely). Thus, behavior analysts can extend their work by using objective measures like pathogen cultures or optic markers and by evaluating the subsequent impact on reported illnesses and attendance.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, if soap or hand sanitizers are unavailable, difficult to access, or depleted, employees do not have the opportunity to complete hand hygiene procedures as needed. For example, Fournier and Berry (2012) showed that the availability and placement of a hand hygiene dispenser in a multifaceted treatment package improved hand hygiene compliance among university students. It is noteworthy that sanitizer use was approximately 60% when the prompt and change agent was present but was just 18% when the change agent was absent.…”
Section: Reduced Response Effortmentioning
confidence: 99%
“…Investigators have shown that hand washing is influenced by environmental structures and context, such as automatic sinks (Larson et al, 1991), electronic flushes (Berry et al, 2012), placement of hand sanitizer (Fournier & Berry, 2012), and sink accessibility and number (Venkatesh, Pallin, Kayden, & Schuur, 2011). Berry and colleagues (2012) suggest these design-behavior interactions (DBI) are important variables for explaining and predicting hand washing, particularly the hand-washing differences between women and men.…”
Section: Social Learning Theorymentioning
confidence: 99%
“…The hand sanitizer dispenser plays a significant role to allow individuals to wash/rub their hands using ABHS while on the go. A study by Fournier et al [ 5 ] reported that the use of a strategically positioned hand sanitizer dispenser was successful in raising hand hygiene activity from 1.52% to over 60%. A few types of dispensers such as mechanical, automated with pushbuttons, touchless, etc., are available to dispense the liquid or gaseous sanitizing materials.…”
Section: Introductionmentioning
confidence: 99%